Sejarah dan Keberagaman Budaya Marga Semende di Kabupaten Muara Enim Sumatera Selatan - Alauwiyah, Fatimah; Mulia, Anora Rezky; Amanda, Diva Tri; Wijaya, Tomy; Hudaidah, Hudaidah; Yati, Risa Marta (Universitas Syiah Kuala, 2025)
The Semende clan has a unique history and governance structure in the context of their customs and traditions. This research aims to provide in-depth insight into how the history of the Semende clan, the entry of Islam into Muara Enim which formed social and cultural identity in the Semende community. The method used is the interview method, then the data is processed in the form of descriptions and poured into this article. The results found that the clan system is an important part of the kinship structure in South Sumatra, especially in Semende. The process of spreading this religion occurs through various ways, including through agriculture which allows people to accept the teachings of Islam. Puyang Ambang and Captain Idham are important figures who play a role in the spread of religion and also play a significant role in the history of the Semende people. In 1969 a regional regulation was issued on the division of clans. At the end of 1975, which stipulated the division of Semende into three clans, namely Semende Darat Ulu Clan, Semende Darat Tengah Clan, Semende Darat Laut Clan. Traditional arts, culinary specialties, folk games, and various other cultural practices such as Adat Tunggu Tubang, are an integral part of the cultural wealth of the Semende people.